Pengembangan Aplikasi Presensi QR Code Berbasis Website Dengan Metode Agile - Assyafa, Izza; Budi, Setyo (Jurnal Informatika: Jurnal Pengembangan IT, 2025)
Attendance recording for students at Pondok Pesantren Mahasiswa (PPM) Al-Hikmah Semarang is still conducted manually, making it prone to recording errors and time-consuming when compiling attendance data. This study aims to develop a QR Code-based attendance system to improve the efficiency and accuracy of attendance recording. The method used involves designing and developing a web-based system using the Laravel framework and the Agile methodology. The system is designed to be used by both students and class supervisors during learning activities at the dormitory. The research results show that the system can automate student attendance through QR Code scanning, store data in a structured manner, and provide accurate attendance reports that are easily accessible to the dormitory administrators. Additionally, features such as schedule management, student data management, and attendance reporting based on specific criteria have been implemented to support more effective administration. The system is also equipped with a feature to print attendance recap reports. With the implementation of this system, student attendance management becomes more efficient, transparent, and less prone to errors compared to the previously used manual method.